Handgrip strength as an indicator of decreased cognitive function in the elderly - Alyssa, Nadya Intan; Parwanto, Edy (International Journal of Research in Medical Sciences, 2022)
In the elderly, the aging process occurs which is associated with a decrease in several functions in the body, including cognitive function and musculoskeletal function. According to the Centers for Disease Control (CDC), 1 in 9 elderly’s has decreased cognitive function. This decline in cognitive function is a form of cognitive dysfunction and is a precursor to the symptoms of Alzheimer's disease and other dementias. According to one study, the prevalence of people who were not detected for dementia because they had never undergone a cognitive examination was 61.7%. One of the possible causes is the absence of cognitive examinations in primary health facilities due to the unavailability of fast and easy instruments. Low hand grip strength has been associated with decreased cognitive function, and can be an effective indicator for early detection of cognitive impairment. In addition, hand grip strength can also be a predictor of decreased cognitive function in the elderly. The exact mechanism between decreased motor power and cognitive function is still unclear. Probably caused by the same cause like the presence of neuropathology in brain such as Lewy bodies, amyloid plaques, neurofibrillary tangles, infarction and atrophy.